Policing COVID-19 through procedural informality in Pakistan - Waseem, Zoha (Policing and society, 2021)
How do police officers respond to public emergencies in developing countries where state institutions struggle to protect citizens and officers alike? This paper investigates police response to the COVID-19 crisis in Pakistan and develops an analytical framework of ‘procedural informality’, a condition whereby state policies are constructed and conveyed to state officials with the tacit acceptance that these are likely to be implemented through informal practice. Procedural informality, therefore, is central to official state practice. It is argued that procedural informality manifested itself in Pakistan during the COVID-19 pandemic in three ways: (1) due to a lack of support from the government, it enabled officers to rely on interpersonal connections within the private sector; (2) intra-organisationally, it forced the police to make hasty decisions due to contradictory policies that strained the workforce, but also allowed it to creatively manage demand; and (3) it compelled the police to respond to non-compliance with a heavy hand, whilst equipping them to protect vulnerable communities and maintain individual relationships. In this way, procedural informality enabled the police to try to meet demand with flexibility, which was encouraged and expected by those interacting with the police. Procedural informality moves beyond the formal-informal dichotomy to show how informality facilitates the implementation of formal policy goals, and the operations of street-level bureaucrats, especially during a crisis. This paper contributes to debates on informality within state institutions and in state practice, while providing empirical insights on police response to COVID-19 from a developing country.